Analisis Gaya Kepemimpinan dalam Memotivasi Kinerja Karyawan di Cafe D'real - Rahmah, Dini; Zahwa; Azhwa, Nadya; Assegaf, Sayyid Aflah Widad Sulthan (CV Global Research Publication, 2025)
This research aims to comprehensively analyze the influence and effectiveness of managerial leadership styles on work motivation and employee performance indicators at Cafe D'Real, a cafe business entity facing the challenges of performance fluctuations and high customer complaints regarding waiting times. Utilizing a qualitative research design with an instrumental case study approach, in-depth field data was collected through semi-structured interviews, a three-month participatory observation, and operational document analysis involving nine key informants (manager, supervisor, baristas, and operational staff). Data analysis was conducted using the Miles and Huberman interactive model, which encompasses data reduction, data display, and conclusion drawing/verification. Field findings indicate that the dominant leadership at Cafe D'Real is a transformational style that stimulates professional pride and creative initiative (intellectual stimulation). However, management failed to bridge the hygiene factors based on Herzberg's Theory due to the excessive application of full autonomy (laissez-faire) during peak hours, triggering role ambiguity, violations of Standard Operating Procedures (SOP), and inconsistencies in service time. The conclusion of this study affirms that transformational leadership in the labor-intensive F&B industry requires situational calibration with firm transactional interventions to ensure the consistency of operational standards.